Cognitive cross network design with physical‐layer coding and spatial modulation - Üstünbaş, S.; Basar, E.; Aygölü, Ü. (Institution of Engineering and Technology (IET), 2017)
A cognitive cross network where both primary and secondary users’ receivers are closer to the transmitter of the other user; however, the distances to their own transmitters are too large that a relay is required for a reliable communication, is considered. To this end, the secondary user shares its relay with the primary user (PU) by means of physical‐layer network coding in exchange for access to PU's licensed band. It is assumed that both transmitters and the relay adopt the emerging spatial modulation concept to improve the error performance. Bit error probability of the proposed scheme is analytically derived and supported via computer simulation results.